1992
DOI: 10.1002/mrd.1080320112
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin (SGP‐2) in epididymal luminal fluid and its association with epididymal spermatozoa in androgen‐deprived rats

Abstract: Clusterin is a heterodimeric glycoprotein synthesized and secreted by rat Sertoli cells and epididymal epithelium. The goal of this study was to determine the presence of clusterin in the luminal fluid of the cauda epididymides and its association with the membranes of developing spermatozoa in the presence and absence of androgen. We have previously demonstrated by two-dimensional (2-D) Western blot probing for clusterin that in epididymal fluid the amounts of clusterin were: caput greater than corpus greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…No temporal changes after vasectomy were detected for either mRNA in any region of the epididymis. Consistent with previous studies, the highest levels of Crisp-1 mRNA were found in the corpus and cauda epididymis and for clusterin in the caput epididymis (Cyr and Robaire, 1992;Mattmueller and Hinton, 1992;Roberts et al, 2001).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…No temporal changes after vasectomy were detected for either mRNA in any region of the epididymis. Consistent with previous studies, the highest levels of Crisp-1 mRNA were found in the corpus and cauda epididymis and for clusterin in the caput epididymis (Cyr and Robaire, 1992;Mattmueller and Hinton, 1992;Roberts et al, 2001).…”
Section: Resultssupporting
confidence: 90%
“…by Sertoli cells in the testis and is a major secretory protein of caput epididymis epithelial cells (Sylvester et al, 1984;Mattmueller and Hinton, 1992). Clusterin has been implicated in cell adhesion and aggregation (Silkensen et al, 1999), lipid transport (Burkey et al, 1992), and cell apoptosis (Buttyan et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…TRPM2, or Clusterin, also found in cluster (6,6), is another gene previously hypothesized to be androgen regulated. Mattmueller and Hinton (39) found that the caudal fluid of orchiectomized rats contain increased amounts of Clusterin, compared with control animals. Several kinases such as PCTAIRE-1 and cyclindependent kinase (CDK)-8, which in general are known to play key roles in cell cycle regulation and cell differentiation and have often been targeted for cancer therapy, were also found in this cluster.…”
Section: Genes That Are Repressed In Response To Androgenmentioning
confidence: 98%
“…This association persists until sperm reach the cauda where clusterin dissociates from sperm, perhaps due to proteolytic processing, and is endocytosed by the epididymal epithelium (Hermo et al, 1991;Mattmueller and Hinton, 1991). Clusterin concentrations in cauda fluid increase following orchiectomy suggesting that the secretion, sperm association and processing of clusterin requires androgens (Mattmueller and Hinton, 1992). Many different functions have been proposed for clusterin including involvement in lipid transport, based on nucleotide similarity to apolipoprotein J (de Silva et al, 1990) and putative roles in programmed cell death (Brandyk et al, 1990).…”
Section: Macromolecular Luminal Fluid Microenvironmentmentioning
confidence: 99%